Trophic interactions in an ant nest microcosm: a combined experimental and stable isotope (δ13C/δ15N) approach. Issue 8 (9th December 2015) - Parmentier, Thomas; Bouillon, Steven; Dekoninck, Wouter; Wenseleers, Tom
Abstract : Living in close association with other organisms has proven to be a widespread and successful strategy in nature. Some communities are completely driven by symbiotic associations and therefore, intimate relationships among the partners can be expected. Here, we analyzed in‐depth the food web of a particularly rich community of arthropods found in strict association with European red wood ants ( Formica rufa group). We studied the trophic links between different ant‐associated myrmecophiles and food sources associated with the host ant, but also tested predator–prey links among myrmecophiles themselves. Our approach combined direct feeding tests and stable carbon and nitrogen isotope analyses for a large number of myrmecophiles. The results of the direct feeding tests reveal a complex food web. Most myrmecophiles were found to parasitize on ant brood. Moreover, we encountered multiple trophic predator– prey links among the myrmecophiles. The results of the stable isotope analyses complement these findings and indicate the existence of multiple trophic levels and trophic isotopic niche compartmentalization. δ 15 N values were strongly correlated with the trophic levels based on the direct tests, reflecting that δ 15 N values of myrmecophiles increased with higher trophic levels. This strong correlation underlines the strength of stable isotopes as a powerful tool to assess trophic levels. In addition, the stable isotope data suggest that most species only facultatively prey on ant brood. The presence of numerous trophic interactions among symbionts clearly contrasts with the traditional view of social insects nests as offering an enemy‐free space for symbionts. Interestingly, the ant host can indirectly benefit from these interactions because brood predators are also preyed upon by other myrmecophiles. Overall, this study provides unique insights into the complex interactions in a small symbiont microcosm system and suggests that the interactions between host and symbiont might be mediated by other symbionts in the same community.